The Impact of IFRS Changes on Companies’ Financial Indicators - Liutkevičiūtė, Inga; Budrionytė, Ramunė; Subačienė, Rasa (Buhalterinės apskaitos teorija ir praktika, 2021)
The ever-changing economic environment changes the business conditions and performance and requires to reflect the changes on accounting information of legal entities. The development of International Financial Reporting Standards (IFRS) is a dynamic and complex process, which helps to provide fair and true information on legal entities. Although, it’s important to evaluate the changes of accounting standards by preparers of financial statements and the users of the information. The purpose of the research is to determine the impact of significant changes of international financial reporting standards on the financial indicators of the companies during 2017-2020 period. Research methods of comparative analysis of scientific literature and legal acts, content analysis, case analysis, grouping of information, systematization, comparative analysis and generalization were used. Main research results state that in 2017-2020 the key changes were related to three standards: IFRS 9 - Financial Instruments, IFRS 15 - Revenue from Contracts with Customers and IFRS 16 - Leases. The study of the impact of the application of the new standards on the financial indicators of 24 Lithuanian listed companies revealed that the new IFRS 16 had the greatest impact on the financial indicators of the companies. The first time, the application of IFRS 16 had a significant impact on 6 of the 24 companies analysed. There was a negative impact on liquidity and solvency ratios, working capital, return on assets and the turnover of assets.